2013
DOI: 10.1117/1.oe.52.10.107104
|View full text |Cite
|
Sign up to set email alerts
|

Vibration sensor using 2 × 2 fiber optic coupler

Abstract: A simple fiber optic vibration sensor is designed and demonstrated using fiber optic fused 2 × 2 coupler that utilized the principle of reflected light intensity modulation. In order to avoid source signal power fluctuations and fiber bending losses, the rational output (RO) technique is adopted. A calibrated 1-mm linear and high sensitivity of 0.36 a:u:∕mm (2.1 mV∕μm) region of the displacement characteristic curve is considered for vibration measurement. The experimental results show that the sensor is capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Study the displacement response and vibration response of the sensor. Implementation of the rational output method to improve response of the sensor than the 1x2 coupler [34,35] The sensor consists of an LED used as a light source and two numbers of photo-Darlington detectors (PD) of high sensitivity housed in a connector less package used to detect the intensity of light at reference and sensing ends. A simple photo detection circuit is developed for conversion of the modulated intensity of light into its equivalent output voltage signal and a DAQ is employed to record the time domain signals (TDS) corresponding to the reference and sensing arms from which the rational output (RO) is calculated.…”
Section: Fiber Optic Fused 2x2 Couplermentioning
confidence: 99%
See 1 more Smart Citation
“…Study the displacement response and vibration response of the sensor. Implementation of the rational output method to improve response of the sensor than the 1x2 coupler [34,35] The sensor consists of an LED used as a light source and two numbers of photo-Darlington detectors (PD) of high sensitivity housed in a connector less package used to detect the intensity of light at reference and sensing ends. A simple photo detection circuit is developed for conversion of the modulated intensity of light into its equivalent output voltage signal and a DAQ is employed to record the time domain signals (TDS) corresponding to the reference and sensing arms from which the rational output (RO) is calculated.…”
Section: Fiber Optic Fused 2x2 Couplermentioning
confidence: 99%
“…It can be observed that the characteristic curve representing the response of PD2 with respect to the displacement of the reflector from the sensing probe (Figure 11) has a linear region of about 1 mm with a sensitivity of 2.1 mV/μm, whereas the response curve representing the RO has a sensitivity of 0.36a.u/mm. This linear region of both responses can be considered for vibration measurement [34,35]. Fiber Optic Vibration Sensors DOI: http://dx.doi.org/10.5772/intechopen.94013…”
Section: Fiber Optic Fused 2x2 Couplermentioning
confidence: 99%
“…Unlike the intensity modulation based accelerometers in [12,13], a cantilever is used to compress a length of single mode fiber at the frequency of vibration acceleration, which makes the transmissivity of the compressed part of the fiber vary. Consequently, the intensity of the light propagated in the fiber is modulated by the vibration acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…According to the principle of optical fiber accelerometers, there are four types of optical modulation, namely, wavelength modulation [8,9], phase modulation [7,10], polarization modulation [11] and intensity modulation [12,13], in which the intensity modulation based accelerometer is realized by micro-bend of fiber or micro-displacement of reflecting mirror. In the above accelerometers, however, the sensor structure and the demodulation system are usually complicated, which may lead to some problems in real application such as high cost, instability.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, optical fibers have attracted a significant amount of research attention in a wide range of applications during the last several decades due to the outstanding advantages of light weight, flexible length, high accuracy, signal transmission security, easy installation, corrosion resistance, and immunity to EM interference [ 7 , 8 ]. These characteristics render them attractive for use in harsh environments where the application of traditional sensors is severely limited [ 9 ].…”
Section: Introductionmentioning
confidence: 99%